Steroid-induced polycystic ovaries in rats: effect of electro-acupuncture on concentrations of endothelin-1 and nerve growth factor (NGF), and expression of NGF mRNA in the ovaries, the adrenal glands, and the central nervous system - Aloe Luigi; Cajander Stefan; Lundeberg Thomas; Stener-Victorin Elisabet; Manni Luigi; Waldenström Urban; Janson Per (Reproductive Biology and Endocrinology, 2003)
Abstract Previous studies on the effect of repeated electro-acupuncture (EA) treatments in rats with steriod-induced polycystic ovaries (PCO), EA has been shown to modulate nerve growth factor (NGF) concentration in the ovaries as well as corticotropin releasing factor (CRF) in the median eminence (ME). In the present study we tested the hypothesis that repeated EA treatments modulates sympathetic nerve activity in rats with PCO. This was done by analysing endothelin-1 (ET-1), a potent vasoconstrictor involved in ovarian functions, as well as NGF and NGF mRNA expression involved in the pathophysiological process underlying steroid-induced PCO. The main result in the present study was that concentrations of ET-1 in the ovaries were significantly lower in the PCO group receiving EA compared with the healthy control group (p < 0.05). In the hypothalamus, however, ET-1 concentrations were found to be significantly higher in the PCO group receiving EA than in the healthy control group (p < 0.05). Concentrations of ovarian NGF protein were significantly higher in the PCO control group compared with the healthy control group (p < 0.001), and these concentrations decreased significantly after repeated EA treatments compared with those in the PCO control group (p < 0.05) and were found to be the same as those in the healthy control group. In conclusion, these results indicate that EA modulates the neuroendocrinological state of the ovaries, most likely by modulating the sympathetic nerve activity in the ovaries, which may be a factor in the maintenance of steroid-induced PCO.